Soil organic matter depletion as a major threat to agricultural intensification in the highlands of Ethiopia - Laetitia (Christy) , Christina; Elias, Eyasu; G. Selassie, Yihenew; Gebresamuel, Girmay; Tsegaye, Asrat; Hundessa, Feyisa; Tolla, Mekonnen; Mamuye, Melkamu; Yemane, Gebremeskel; Mengistu, Seyoum (Ethiopian Journal of Science and Technology, 2025)
Agriculture is considered as the backbone of Ethiopian economy. The government promotes rural development through policies that enhance intensive and commercially-oriented agriculture. Soil quality may be the bottleneck of these ambitions as more than half of the agricultural land shows signs of land degradation. Soil organic carbon (SOC) contents are a key aspect of soil quality, where relatively high SOC contents indicate better water holding capacity, nutrient retention capacity and better structure of the soil. In this research, SOC balances were used as indicator for short and midterm changes in SOC contents. SOC balances were calculated using data collected from 6914 fields for three years (2012-2014) using a simple input-out approach. On average, SOC balances were three tons per hectare per year. This equals 4 to 7% of the total soil organic carbon stock, which varied according to regions and cropping systems. SOC depletion rates were high in the mountainous and high cultivation intensity sites in central and northern Ethiopia where cereal based cropping systems dominates. Under the current practice, soils will eventually become exhausted and lose their productivity. This alarming trend could be reversed by integrating organic matter and nutrient management strategies and by providing alternative sources for feed and fuel supply of the community.